Profiling of REST-Dependent microRNAs Reveals Dynamic Modes of Expression - Gao, Zhengliang; Ding, Peiguo; Hsieh, Jenny (Frontiers in Neuroscience, 2012)
Multipotent neural stem cells (NSCs) possess the ability to self-renew and differentiate into both neurons and glia. However, the detailed mechanisms underlying NSC fate decisions are not well understood. Recent work suggest that the interaction between cell-type specific transcription factors and microRNAs (miRNAs) is important as resident neural stem/progenitor cells give rise to functionally mature neurons. Recently, we demonstrated that the transcriptional repressor REST (RE1-silencing transcription factor) is essential to prevent precocious neuronal differentiation and maintain NSC self-renewal in the adult hippocampus. Here we show that REST is required for orchestrating the expression of distinct subsets of miRNAs in primary mouse NSC cultures, a physiologically relevant cell type. Using miRNA array profiling, we identified known REST-regulated miRNA genes, as well as previously uncharacterized REST-dependent miRNAs. Interestingly, REST-regulated miRNAs undergo dynamic expression changes under differentiation conditions over time, but not under proliferation conditions. These results suggest that REST functions in a context-dependent manner through its target miRNAs for mediating neuronal production.